1993
DOI: 10.1007/bf00124363
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of ulapualides, a new family of tris-oxazole-containing macrolide ionophores from marine nudibranchs. A molecular mechanics study

Abstract: A molecular mechanics study of the marine metabolite ulapualide A, which is suggested to have ionophoric properties, has been carried out on various metal chelated complexes in order to predict the stereochemistry of the natural product. The results suggest a stereochemistry for ulapualide A which is closely similar to structurally related marine metabolites, whose stereochemistries have been established by X-ray crystallography and by partial synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…11 The juxtaposition of several nitrogen and oxygen ligandbinding sites in the ulapualides encouraged us earlier to carry out a molecular mechanics study of a hypothetical metal-chelated complex of ulapualide A. 12 This study led us to assign the relative stereochemistry shown in structure 8 for ulapualide A, 13 and in 1998 we described a total synthesis of this compound. Much to our chagrin, although the synthetic ulapualide A showed identical chromatographic behaviour, as well as chiroptical and 1 H NMR spectroscopic data, with those of the natural product, very small differences were observed in the 13 C NMR spectra, associated with the C32-C34 portions, of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…11 The juxtaposition of several nitrogen and oxygen ligandbinding sites in the ulapualides encouraged us earlier to carry out a molecular mechanics study of a hypothetical metal-chelated complex of ulapualide A. 12 This study led us to assign the relative stereochemistry shown in structure 8 for ulapualide A, 13 and in 1998 we described a total synthesis of this compound. Much to our chagrin, although the synthetic ulapualide A showed identical chromatographic behaviour, as well as chiroptical and 1 H NMR spectroscopic data, with those of the natural product, very small differences were observed in the 13 C NMR spectra, associated with the C32-C34 portions, of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…behave as ionophores, using the several oxazole nitrogen and side chain oxygen ligand binding sites present in their structures. 6 The combination of a unique chemical structure with novel biological properties encouraged us to examine a total synthesis of the founder member, ulapualide A (1), of this family of marine metabolites and to examine their ionophore properties. In the immediately preceding paper 7 we described concise synthetic routes to the tris-oxazole ring system found in the natural product, and in this paper we describe the extension of this work culminating in a total synthesis of ulapualide A, with the relative stereochemistry shown in structure 1.…”
mentioning
confidence: 99%
“…Based on a molecular mechanics modeling study performed on a Co III –ulapualide A chelate and comparison with the scytophycins, Pattenden et al proposed the configurational assignment shown in Scheme (isomer‐ 13 ). 41, 42 However, recent chemical degradation and synthetic studies by Fusetani and Panek on the mycalolides have shown that the C20–C35 segment of ulapualide B has the same configuration as the corresponding C20–C35 segment of the mycalolides 16d. The full stereostructure of mycalolide A ( 12 ) has been unambiguously confirmed by Panek et al by total synthesis (Section 2.7), whereas the Pattenden group have synthesized isomer‐ 13 , which proved to be a diastereoisomer of ulapualide A.…”
Section: Total Synthesismentioning
confidence: 99%